Überlieferte Sprache und Technische Sprache - Heidegger, Martin 1889-1976; Heidegger, Hermann 1920-2020 (St. Gallen Erker, 1989)
On July 18, 1962, Martin Heidegger delivered a lecture entitled Überlieferte Sprache und Technische Sprache (1) (Traditional Language and Technological Language) in which he argues that the opposition between these languages concerns our very essence.
Keywords: Philosophy; Linguistics